THE ORIGINS AND DEVELOPMENT OF STRATEGIC MANAGEMENT "KNOWLEDGE": A HISTORICAL PERSPECTIVE - Lewa, Peter M.; Narikae, Parmain Ole (European Journal of Business and Strategic Management, 2017)
This paper examines the issue of the historical development of the knowledge dubbed strategic management. Strategic management is a field of study, academic discipline and a business area. Much knowledge has been generated during the different phases of the development of the concept or discipline. This has benefited many organizations. Knowledge management is crucial for development and transformation of societies and quality of life. Over the years, for the purposes of accelerating progress and development, a lot of knowledge has been generated in this area of academic and practical interest. This paper examines this specific area of academic endeavour popularly called strategic management. Nearly every organization on the globe engages in some form of strategic planning or management. This paper examines the development of this very important area of knowledge and attempts to provide the critical issues in the historical development of the discipline in the context of the requisite knowledge management. Understanding the critical dimensions in the development of the discipline provides readers, practitioners and policy makers with knowledge that if utilized properly will help organizations achieve growth and development from the most advantageous point in their operations. This is the essence of strategic management. This paper utilized secondary data that was obtained from desk research but data was also collected using a checklist, focus group interview and a brain storming session with Doctor of Business Administration students (DBA Cohort 2) at the United States International University (USIU) - Africa in Spring 2014.